The Influential Factors and Characteristics of Tight Sandstone Gas Reservoir: A Case Study in Ordos Basin in China. (29th December 2020) - Ren, Dazhong; Yang, Fu; Li, Rongxi; Li, Yuhong; Liu, Dengke
Abstract : To analyze the impact of the factors on physical properties and the mechanism of tightness as well as favorable accumulation space of tight sandstone reservoir, comprehensive analysis is conducted using various kinds of experiments. The results show that the predominant rock type is medium-coarse grained lithic quartzarenite, and the main accumulating space is the dissolved secondary pores. Reservoir pore-throat structures can be divided into four categories. Based on morphologies and parameters which derived from capillary pressure curves, the physical properties rank in the following descending sequence: Type   I > Type   II > Type   III > Type   IV . The reservoir quality is influenced by both sedimentation and diagenesis synthetically. The underwater distributary channel is the dominant space for favorable reservoir. Compaction and cementation play dominant roles in the reduction of permeability. The loss of primary pores caused by both those diagenesis are 20.52% and 16.91%, respectively. Secondary pores formed by dissolution improve the reservoir quality by increase the porosity (2.68%). This suggests that weak diagenesis greatly contributes to the improvement of reservoir quality.